2021
DOI: 10.1038/s41467-021-22284-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular macromolecules-tethered DNA walking indexing to explore nanoenvironments of chromatin modifications

Abstract: Exploring spatial organization and relationship of diverse biomolecules within cellular nanoenvironments is important to elucidate the fundamental processes of life. However, it remains methodologically challenging. Herein, we report a molecular recognition mechanism cellular macromolecules-tethered DNA walking indexing (Cell-TALKING) to probe the nanoenvironments containing diverse chromatin modifications. As an example, we characterize the nanoenvironments of three DNA modifications around one histone posttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…ATP and propargylamine were used to prepare ATP-γ-alkyne. ATP disodium salt (4.9 mM) and propargylamine (245 mM) were dissolved in water. The solution pH was adjusted to 6.0 with dilute HCl. Also, then EDC-HCl (490 mM) was added to the above solution and the mixture was stirred for 24 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…ATP and propargylamine were used to prepare ATP-γ-alkyne. ATP disodium salt (4.9 mM) and propargylamine (245 mM) were dissolved in water. The solution pH was adjusted to 6.0 with dilute HCl. Also, then EDC-HCl (490 mM) was added to the above solution and the mixture was stirred for 24 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[56a] Zhao et al reported a molecular recognition mechanism cellular macromoleculestethered DNA walking indexing (Cell-TALKING) to probe the nano environments containing diverse chromatin modifications. [64] Taking the exosome as 3D track and split aptamers as a recognition element, a self-serviced-track DNA walker (STDW) was designed for wash-free and highly sensitive detection of tumor exosomes by glycoprotein profiling. [65] To further explore the functionality of the continuously actuating DNA nanorobot in cell manipulation, our group recently developed an autonomous DNA nanorobot by extending the track of DNA nanorobots from fixed DNA origami to the floating receptors in the fluidic cell membrane (Figure 6d).…”
Section: Continuously Actuating Dna Nanorobots Enabling Autonomous Mo...mentioning
confidence: 99%
“…Zhao et al. reported a molecular recognition mechanism cellular macromolecules‐tethered DNA walking indexing (Cell‐TALKING) to probe the nano environments containing diverse chromatin modifications [64] . Taking the exosome as 3D track and split aptamers as a recognition element, a self‐serviced‐track DNA walker (STDW) was designed for wash‐free and highly sensitive detection of tumor exosomes by glycoprotein profiling [65] …”
Section: Designer Dna Nanorobots Performing Desirable Biomedical Func...mentioning
confidence: 99%
“…Chen’s group introduced a structure of macromolecules-tethered DNA walking indexing to probe the biological environment around multi-DNA-modified histone post-translational modification (PTM). They indicated that this one-to-many nanoenvironments detection was expected to be used in clinical applications [ 106 ]. Furthermore, DNA can also be applied for structure inspection so as to better understand life activities.…”
Section: Other Applicationsmentioning
confidence: 99%